Some properties of the concurrent grammars - Mavlankulov, Gairatzhan; Othman, Mohamed; Selamat, Mohd Hasan; Turaev, Sherzod (Springer Science+Business Media Singapore 2014, 2014)
Petri nets are becoming one of the most important mathematical tools in Computer Science. In this paper, we study some mathematical properties of concurrent grammars which are controlled by Petri nets under parallel firing strategies, where transitions of Petri nets fire simultaneously in different modes.We propose a notion of concurrent context-free grammar which is a similar case of the context-free Petri nets under parallel firing strategy, where parallel firing modes of context-free Petri nets were converted to rule applications in context-free grammars and we investigate their properties.